Denmark : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
The staff report for the 2004 Article IV Consultation on Denmark focuses on economic developments and policies. Labor market reforms led to a sustained increase in structural employment, while careful fiscal policy in the context of a clear medium-term sustainability strategy delivered budget surpluses and a steady decline in government debt as a share of GDP. Fiscal policy in Denmark is based on a medium-term strategy to accommodate the pressures from an aging population while maintaining the welfare state without increasing taxes.